The U.S. Maritime Policy Towards the South China Sea During President Barack Obama’s Tenure (2009-2017) - Obeed, Dr. Ali Talib (Thi Qar Arts Journal, 2024)
The South China Sea is one of the most important and contentious bodies of water in the world. It is a complex geopolitical area that has often been a source of conflict between nations due to its significance, geographical location, and rich resources. Tensions between the United States and China over the South China Sea have gradually escalated to a strategic level because of China’s expansionist policies in the disputed islands, including reclaiming land and building military bases. The United States has grown increasingly concerned about China’s potential to gain effective control over the region, which is of strategic, political, and economic importance to the U.S. and its allies2. This has led to direct confrontations between China and the United States, despite the U.S. strategy still relying on containment to protect its allies in the region and limit Chinese influence. The South China Sea holds significant strategic and economic importance due to its geographical location at the intersection of the world’s busiest maritime routes. More than half of global trade passes through it. The importance of this research lies in the development of U.S. naval power amidst extensive global openness. Seas have become crucial for stability, national security, economy, and extensive trade, especially after the close economic interconnection between countries. The seas are now fundamentally important due to their dense use as primary routes for transporting goods and energy materials. This shift has changed the nature of maritime importance, as threats to the seas now not only threaten the security of nations but also their welfare and economy Keywords: U.S. Navy, South China Sea, Naval Power.